Additional Damping Control of a Hybrid Multi-infeed DC System with a Wind Farm - Li, Congshan; Fang, Yan; He, Ping; Li, Yikai; Sheng, Tingyu (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: In a hybrid multi-infeed direct current (HMIDC) system, the interaction between the AC and DC systems has an influence on the damping characteristics of the system, while a doubly-fed induction generator (DFIG) based wind turbine connected to the grid complicates the coupling between AC and DC. Objective: Based on the basic principles of wind power generation and low-frequency oscillation (LFO), a DFIG -based wind turbine is connected to the LCC-HVDC side and VSC-HVSC side of an HMIDC system to study the influence of the oscillation mode on a hybrid system with different wind power access locations, and two kinds of additional DC damping controllers have been designed to suppress the LFO. Moreover, the effects of different additional DC damping controllers on the suppression of the LFO in the system have also been compared. Methods: First, the total least squares- estimation of signal parameters via rotational invariance techniques (TLS-ESPRIT) was used to obtain the system’s oscillation mode. Second, the transfer function was determined by the Butterworth bandpass filter. Third, the LCC-HVDC and VSC-HVDC additional damping controllers were designed based on the H2/H∞ hybrid control theory. Results: The designed additional DC damping controller showed a good suppression effect on LFO in the HMIDC system and could meet the system damping deficit. The effect of the LCC-HVDC additional damping controller was observed to be better than that of VSC-HVDC. Conclusion: Through a simulation analysis on PSCAD/EMTDC simulation software, the effectiveness of the designed additional DC damping controller has been verified.
Keywords: least squares-estimation